Trust and Growth: A Shaky Relationship - Niclas Berggren; Mikael Elinder; Henrik Jordahl (Research Institute of Industrial Economics (IFN), 2007)
We conduct an extensive robustness analysis of the relationship between trust and growth by investigating a later time period and a bigger sample than in previous studies. In addition to robustness tests that focus on model uncertainty, we systematize the investigation of outlier influence on the results by using the robust estimation technique Least Trimmed Squares. We find that when outliers (especially China) are removed, the trust-growth relationship is no longer robust. On average, the trust coefficient is half as large as in previous findings.
Keywords: O40; Z13; 330; Trust; Growth; Robustness; Social Capital; Outliers; Vertrauen; Wirtschaftswachstum; Social Capital; Schätzung; Robustes Verfahren